Comparing the service experience of satisfied and non-satisfied customers in the context of wine tasting rooms using the SERVQUAL model. Issue 2 (16th September 2019) - Haverila, Matti; Haverila, Kai; Arora, Mehak
Abstract : Purpose: The purpose of this study is to compare satisfied and non-satisfied customers in the context of wine tasting rooms using the SERVQUAL model and to examine the relationships in the model in terms of service experience to better understand customer needs. Design/methodology/approach: The data used in this study were derived from a survey conducted among wineries in British Columbia, Canada. Analysis of survey results using the partial least squares structural equation modeling was undertaken. Sample size was 402. Findings: The findings show that the SERVQUAL constructs that had the most impact on customer satisfaction and dissatisfaction were tangibility and assurance. Somewhat surprisingly, the perceived value for money construct was not significantly related to customer satisfaction but was significantly related to repurchase intent. Furthermore, all SERVQUAL constructs, except the reliability construct, were significantly related to customer satisfaction. Originality/value: This study provides an overview of how wineries can improve their services to increase the number of satisfied customers.